Moved by Observing the Love of Others: Kama Muta Evoked Through Media Fosters Humanization of Out-Groups - Blomster Lyshol, Johanna K.; Thomsen, Lotte; Seibt, Beate (Frontiers in Psychology, 2020)
People often view out-groups as less human than their in-group. Some media video content is heart-warming, and leaves one feeling touched or moved. Recent research indicates that this reflects a positive social emotion, kama muta, which is evoked by a sudden increase in interpersonal closeness, specifically by the relational model of communal sharing. Because forming strong, close and communal bonds exemplifies valued human qualities, and because other humans are our primary target partners of communal sharing, we predicted that feeling kama muta in response to observing communal sharing among out-group strangers would make people view out-groups as more human. In Study 1 we replicated a model obtained through a large exploratory preliminary study which indicated that videos depicting out-group members enacting communal sharing evoked kama muta and increased protagonist humanization. This, in turn, led to decreased blatant dehumanization of the entire out-group via perceived out-group warmth and motivation to develop a communal sharing relationship with the protagonist. The pre-registered Study 2 further tested our model, demonstrating 1) that the relationship between protagonist humanization and kama muta is bidirectional such that baseline humanization of the protagonist also increases feelings of kama muta in response to acts of communal sharing; 2) that watching videos of communal sharing, as compared to funny videos, increased protagonist humanization; and 3) that kama muta videos, compared to funny videos, had an indirect effect on the reduction of out-group blatant dehumanization, which was mediated by protagonist humanization and out-group warmth.